Antimicrobial Activity, Microstructure, Mechanical, and Barrier Properties of Cassava Starch Composite Films Supplemented With Geranium Essential Oil - Wang, Bin; Yan, Shouxin; Qiu, Lizhong; Gao, Wei; Kang, Xuemin; Yu, Bin; Liu, Pengfei; Cui, Bo; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
In this study, we prepared cassava starch-based films by the casting method. Afterward, the effects of geranium essential oil (GEO) on the prepared films’ physicochemical, morphology, and antibacterial properties were revealed. We found that the thickness and elongation at the break of cassava starch films increased with increasing GEO concentration (from 0.5, 1, and 2%). However, with increasing GEO concentration, the water content, water vapor permeability, and tensile strength of the prepared films’ decreased. Further, the addition of GEO increased the surface roughness, opacity, and antibacterial properties of the prepared films. In summary, this study provides a theory for cassava starch-based films as a biological packaging material.